Assessing the quality of early childhood education and care in Australia: Challenges and opportunities - Cohrssen, Caroline; de Rosnay, Marc; Garvis, Susanne; Neilsen-Hewett, Cathrine (Frontiers in Education, 2023)
While access to quality education in early childhood is an international priority, the characteristics of quality continue to be debated. In the Australian context, differing views on the characteristics of quality may be a result of differing stakeholder priorities. Divergent notions of quality may lead to initiatives that emphasize educator practice and frame a dominant discourse that situates responsibility for enactment of quality at Early Childhood Education and Care (ECEC) service room level. Challenges arising from initiatives driving increased access to ECEC coinciding with workforce shortages are addressed. National longitudinal research is needed to determine the impact of participation in ECEC on child outcomes, as is ECEC quality assessment across regions and jurisdictions over time. Prior to this, stakeholder conversations are needed to achieve consensus on the characteristics of quality. This could lead to the development of an instrument for assessing quality that is systemically relevant and could inform evidence-based decision making by ECEC teachers and educators, primary caregivers, regulators, researchers and policy makers to distribute accountability for quality across the ECEC system.